Task Distribution Mechanism for Effective Collaboration in Virtual Environments: Task Distribution Mechanism for Effective Collaboration in Virtual Environments - Khalid, Shah; Ullah, Sehat; Alam, Aftab (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Collaborative Virtual Environments (CVEs) are computer generated worlds where two or more users can simultaneously interact with synthetic objects to perform a task. User performance is one of the main issues caused by either loose coordination, less awareness or communication among collaborating users. In this paper, a new model for task distribution is proposed, in which task distribution strategy among multiple users in CVEs is defined. The model assigns the task to collaborating users in CVEs either on static or dynamic basis. In static distribution there exists loose dependency and requires less communication during task realization whereas in dynamic distribution users are more dependent on each other and thus require more communication. In order to study the effect of static and dynamic task distribution strategies on user’s performance in CVEs, a collaborative virtual environment is developed where twenty four (24) teams (each consists of two users) perform a task in collaboration under both strategies (static and dynamic). Results reveal that static distribution is more effective and increases users’ performance in CVEs. The outcome of this work will help the development of effective CVEs in the field of virtual assembly, repair, education and entertainment.